Medidas de urgência no âmbito recursal - Bonilha, Márcia Giangiacomo (2008)
This paper aims to study the urgency measures within the appeal sphere. The urgency measures are differentiated injunction; in other words, alternate injunctions to the common, ordinary procedure. Due to the rediscovery we have been experiencing pursuant to the relation of the procedural law with the material law, such measures have revealed themselves as increasingly important to the acclaimed effectiveness of the jurisdictional injunction, to the concrete execution of the material law; its performance is not restricted to the proceedings in the first level of jurisdiction. The preliminary injunction, the temporary injunction and the restraining orders in general constitute urgency measures, without any sort of prohibition so that any of them may be granted within the appeal sphere. There are express provisions in the legal text which regulate the granting of urgency measures within the appeal scope. Thus, in this work, both typical and atypical measures are treated, emphasizing that the judging entity is not a mere applier of the law, but a central figure in the judicial-procedural relation, holder of the power / duty to ensure that the jurisdictional injunction is in conformance with the sacred principles and values of our legal system